Statistics: for bba 2nd semester, including solutions - hints of all exercise problems (Kalyani Publishers, 2016)
Statistics: for bba 2nd semester, including solutions/hints of all exercise problems; multiple choice and short answer / Nag, N.K. -- Kolkata: Kalyani Publishers, 2016 519.5 N147e3 3rd ed No. of Copies : 1